Impact of socioeconomic status on chronic obstructive pulmonary disease prognosis: a national cohort study - Hyewon Lee; Hyewon Lee; Jiyun Jung; Hee-Young Yoon (Frontiers in Medicine)
BackgroundChronic obstructive pulmonary disease (COPD) is a major cause of global morbidity and mortality, with socioeconomic status (SES) playing a significant role in disease outcomes. While the impact of individual SES on COPD has been reported, the influence of both individual and neighborhood SES on clinical outcomes remains unclear. We aimed to evaluate the association between SES and COPD outcomes.MethodWe conducted a retrospective cohort study using 2015–2018 data from the Korean National Health Insurance Service-National Sample Cohort, linked with census data. SES was assessed at both individual (income, insurance type) and neighborhood levels (residential area, elderly proportion, education level, gross regional domestic product, and total population density). Outcomes included overall mortality and hospitalization, which were evaluated using Cox proportional hazard models adjusted for demographic and air pollution.ResultsAmong 12,820 patients (mean age 63.5 years, 47.2% male), higher income was significantly associated with lower mortality risk (hazard ratio [HR] = 0.961, 95% confidence interval [CI] = 0.936–0.986) in the adjusted model. Suburban residence was associated with increased mortality risk (HR = 1.432, 95% CI = 1.089–1.884), while rural residence was not significant after adjustment. For hospitalization, higher income was also significantly associated with a lower risk (HR = 0.987, 95% CI = 0.979–0.995). Suburban (HR = 1.097, 95% CI = 1.013–1.187) and rural (HR = 1.138, 95% CI = 1.046–1.239) residence also remained significantly associated with increased hospitalization risk in the adjusted models. Additionally, a higher proportion of older adults (HR = 1.010, 95% CI = 1.004–1.016) and lower educational attainment (HR = 0.992, 95% CI = 0.989–0.995) were also significantly associated with hospitalization risk.ConclusionThese findings suggest that individual SES is associated with both mortality and hospitalization among patients with COPD, while neighborhood SES influences hospitalization but not mortality after adjustment.